2004
DOI: 10.1191/0269216304pm913oa
|View full text |Cite
|
Sign up to set email alerts
|

Evolving spinal analgesia practice in palliative care

Abstract: Intraspinal analgesia can be helpful in some patients with intractable pain. Over 15 years palliative care professionals evolved their spinals policy through a repeated series of evaluations, discussions and literature reviews. One hundred intraspinal lines were then reviewed. Notable changes in policy were the switch from epidurals to intrathecals, and the insertion of lines during working hours rather than as emergencies. Our efficacy, and frequency of adverse effects, is equal or better to published studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…These are considered for patients with advanced cancer whose pain cannot be controlled with systemic medication, or the use of systemic medication is limited by unacceptable side effects at doses below those required to give adequate pain relief. A neuroaxial infusion, either epidurally or intrathecally, gives good control in the majority of cases 67. The most effective drugs to infuse neuroaxially are opioids.…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…These are considered for patients with advanced cancer whose pain cannot be controlled with systemic medication, or the use of systemic medication is limited by unacceptable side effects at doses below those required to give adequate pain relief. A neuroaxial infusion, either epidurally or intrathecally, gives good control in the majority of cases 67. The most effective drugs to infuse neuroaxially are opioids.…”
Section: Interventional Proceduresmentioning
confidence: 99%
“…Clonidine was added to only one patient's therapy. Baker et al [ 29 ] performed a 15-year retrospective survey of 100 spinal catheters in the treatment of cancer and reported on clinical changes associated with switching from epidural to intrathecal therapy. Over the study time period, 81 patients had intrathecal treatments consisting mainly of diamorphine and bupivacaine.…”
Section: La Agentsmentioning
confidence: 99%
“…Tumber and Fitzgibbon [ 33 ] described a patient who required a "cocktail" of continuous intrathecal medications that included clonidine for pain control due to his inoperable sacral chordoma. In the review by Baker et al [ 29 ], clonidine was reportedly used in approximately one third of patients for better pain control. De Kock et al [ 34• ] evaluated the postoperative use of clonidine in 60 patients who underwent elective colonic resections for adenocarcinoma and found that intrathecal clonidine had transitory analgesic effects along with a greater reduction of secondary hyperalgesia and residual discomfort postoperatively, compared with the bupivacaine or saline group.…”
Section: α 2-adrenergic Agonistsmentioning
confidence: 99%
“…Bard, Inc., Murray Hill, NJ). With appropriate infection control measures, including the use of antimicrobial filters and meticulous exit site care, tunneled IT or epidural catheters can be used for months to years [5,6] The catheter generally is not sutured internally so it can be readily removed in the office if necessary. An advantage of the exteriorized system is that non-pain specialist palliative care clinicians, including those in a home hospice setting, may be become proficient in its management with minimal training.…”
Section: Tunneled Intrathecal Cathetermentioning
confidence: 99%